Microresearch: Promoting Scholarly Activity That Addresses Health Disparities in Rural Health Professional Education Programs - Glenn, Lynn Engelberg; Simon, Lisa; Smith, Veronica S; Longenecker, Randall L; Schmitz, David; Patterson, Davis G (Journal of health care for the poor and underserved, 2020)
Microresearch is an innovative, mentored research experience, originally developed in Africa and adapted for U.S. health professional trainees preparing for rural primary care practice. This report describes program elements (funding, mentorship, and peer support) that others may replicate to develop research and leadership skills through community engagement to address health disparities.